1995
DOI: 10.1007/bf02193084
|View full text |Cite
|
Sign up to set email alerts
|

Impaired saccadic eye movements on stationary targets in patients with schizophrenia spectrum disorder

Abstract: This study examined tracking eye movements on predetermined stationary targets in patients with schizophrenia spectrum disorder. The targets were 8 black points or 8 arabic-numbered points placed on the circumference of a circle. Self-paced eye movements during clockwise tracking of these points by 23 patients and 23 normal controls were recorded using an infrared eye-mark recorder. Eye movements were analyzed at two settings: firstly, when "fixation point" was defined as a point at which a gaze was held for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, the present result may provide additional evidence for impaired neurocognitive function in schizophrenia. Consistent with this, Matsui et al (1995Matsui et al ( , 1997. reported that patients with schizophrenia showed more deviant scan paths than normal controls, and that some patients accurately tracked target points at the100-ms setting but not at the 200-ms setting.…”
Section: Discussion S Exploratory Eye Movement On the Different Sizesmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, the present result may provide additional evidence for impaired neurocognitive function in schizophrenia. Consistent with this, Matsui et al (1995Matsui et al ( , 1997. reported that patients with schizophrenia showed more deviant scan paths than normal controls, and that some patients accurately tracked target points at the100-ms setting but not at the 200-ms setting.…”
Section: Discussion S Exploratory Eye Movement On the Different Sizesmentioning
confidence: 65%
“…In most previous studies on exploratory eye movement, a fixation point has been defined as a point at which a gaze is held for longer than 200 ms. However, Matsui et al (1995Matsui et al ( , 1997. found that some schizophrenic patients viewed the targets in a shorter period during saccadic tracking task.…”
Section: Introductionmentioning
confidence: 96%